METACRYPHAEUS TUBERCULATUS AND METACRYPHAEUS AUSTRALIS (TRILOBITA, PHACOPIDA) FROM THE DEVONIAN OF THE PARANÁ BASIN: TAXONOMY AND PALEOBIOGEOGRAPHY (Ameghiniana, 2016)
Calmoniid trilobites of the genus Metacryphaeus Reed include M. tuberculatus (Kozlowski), M. kegeli Carvalho, Edgecombe and Lieberman, M. meloi Carvalho, Edgecombe and Lieberman, M. rotundatus (Kozlowski), M. giganteus (Ulrich), M. convexus (Ulrich), M. curvigena Lieberman, M. branisai Lieberman, M. caffer (Salter), M. australis (Clarke), and M. allardyceae (Clarke). The geographic distribution of this genus comprises areas of Gondwana, including Bolivia, Peru, Brazil, the Falkland Islands, and South Africa. This study reports a new occurrence of M. tuberculatus in the Paraná Basin (Goiás and Paraná states, Brazil), in both the Alto Garças and the Apucarana sub-basins. Metacryphaeus tuberculatus was compared with all Metacryphaeus species and, especially, with M. australis, which also represents a new record for the Paraná Basin. These new records of M. tuberculatus imply a different dispersion interpretation from that which is known through the literature. Metacryphaeus tuberculatus seems to have originated during the Early Devonian and lived in areas such as Bolivia, Peru, and the Apucarana Sub-basin (Paraná Basin, Brazil). The dispersion between these areas is probably related to the Emsian transgression. During the Givetian, the species presumably migrated towards the Alto Garças Sub-basin (Paraná Basin, Brazil) and the Parnaíba Basin. These facts provide an alternative paleogeographic interpretation to that presented by Tropidoleptus Hall and Exaesiodiscus Moore and Jeffords in Gondwana and suggest a different pattern of migration during the Devonian of Brazil. Resumen. METACRYPHAEUS TUBERCULATUS Y METACRYPHAEUS AUSTRALIS (TRILOBITA, PHACOPIDA) DEL DEVÓNICO DE LA CUENCA DEL PARANÁ: TAXONOMIA Y PALEOBIOGEOGRAFÍA. Los trilobites calmónidos del género Metacryphaeus Reed incluyen M. tuberculatus (Kozlowski), M. kegeli Carvalho, Edgecombe y Lieberman, M. meloi Carvalho, Edgecombe y Lieberman, M. rotundatus (Kozlowski), M. giganteus (Ulrich), M. convexus (Ulrich), M. curvigena Lieberman, M. branisai Lieberman, M. caffer (Salter), M. australis (Clarke) y M. allardyceae (Clarke). La distribución geográfica de este género incluye áreas de Gondwana como Bolivia, Perú, Brasil, las Islas Malvinas y Sudáfrica. Este estudio reporta una nueva ocurrencia de M. tuberculatus en la Cuenca del Paraná (estados de Goiás y Paraná, Brasil), tanto en la sub-cuenca de Alto Garças como en la de Apucarana. Metacryphaeus tuberculatus fue comparado con todas las especies de Metacryphaeus, especialmente M. australis, que también presenta un nuevo registro en la Cuenca del Paraná. Estos nuevos registros de M. tuberculatus implican una dispersión diferente de la que se conoce en la literatura. Metacryphaeus tuberculatus parece tener su origen durante el Devónico Temprano en zonas como Bolivia, Perú y en la Sub-cuenca de Apucarana (Cuenca del Paraná, Brasil). Probablemente la dispersión entre estas áreas está relacionada con la transgresión Emsiense. Durante el Givetiense, la especie probablemente emigra a la Sub-cuenca Alto Garças (Cuenca del Paraná, Brasil) y a la Cuenca del Parnaíba, donde tiene registros. Estos hechos proporcionan una interpretación paleogeográfica diferente en comparación con la presentada por Tropidoleptus Hall y Exaesiodiscus Moore and Jeffords en Gondwana y también sugieren un patrón diferente de migración para el Devónico de Brasil.